Phenological trends in southern Spain: A response to climate change - García-Mozo, H.; Mestre, a; Galan, C. (Agricultural and Forest Meteorology, 2010)
The impact of climate change, and particularly of climate warming, is being tracked in many physical and biological systems. Plant phenology is seen as one of the most important bio-indicators, since trends can provide considerable temporal and spatial information regarding ongoing changes. Analyses performed at six sites in southern Spain from 1986 to the present have focused on vegetative and overall reproductive phenology in Olea europaea L., and Vitis vinifera L. and in various species of Quercus spp. and Poaceae. Early results suggest that trends in ﬂowering patterns derived from ﬁeld phenological observations were similar to trends in aerobiological data for most study species, and indicate a trend towards earlier foliation, ﬂowering and fruit ripening. This advance is more evident in arboreal than in herbaceous species. Statistical analysis showed temperature increase was the major factor affecting earlier foliation, ﬂowering and fruit ripening, as well as prompting delayed leaf fall. Herbaceous species were more affected than trees by changes in rainfall records
Keywords: Aerobiology; climate change; Phenology; pollen